2020
DOI: 10.1186/s13570-020-00174-1
|View full text |Cite
|
Sign up to set email alerts
|

Rural households’ perception on the effects of Prosopis juliflora invasion: The case of Amibara District of Afar National Regional State, Ethiopia

Abstract: In Ethiopia, Prosopis juliflora (P. juliflora) becomes one of the worst invasive alien species threatening the livelihood and thus food security of pastoral and agro-pastoral communities. However, up to the present, there have been few studies on the social aspects of the problem. This study explores households’ perceptions about the effects of P. juliflora invasions in Amibara district of Afar National Regional State, Ethiopia. The study used cross-sectional data collected from 130 randomly selected household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…environmental harms [21,30,31] Disrupt ecosystem functioning and services [14,30,32,33] Soil properties and soil seed bank [30,[34][35][36][37][38][39] Hydrology [40] Land use land cover changes [41][42][43][44][45][46] Rangelands, quality, and availability of animal feeds [11,21,30,32,43,47] Productivity of agricultural lands [30,48,49] Loss of biodiversity [30,43,48,50] Invade parts of wildlife reserves and national parks [2,32,35,47,48,51] Human and livestock health [2,13,30,35,43,52,53] Effect economy and overall communities' livelihoods of a country [2,32,…”
Section: Effects Of P Juliflora Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…environmental harms [21,30,31] Disrupt ecosystem functioning and services [14,30,32,33] Soil properties and soil seed bank [30,[34][35][36][37][38][39] Hydrology [40] Land use land cover changes [41][42][43][44][45][46] Rangelands, quality, and availability of animal feeds [11,21,30,32,43,47] Productivity of agricultural lands [30,48,49] Loss of biodiversity [30,43,48,50] Invade parts of wildlife reserves and national parks [2,32,35,47,48,51] Human and livestock health [2,13,30,35,43,52,53] Effect economy and overall communities' livelihoods of a country [2,32,…”
Section: Effects Of P Juliflora Authorsmentioning
confidence: 99%
“…P. juliflora thorns are dangerous and inflict pain that is like being bitten by a snake [21]. For instance, among human injuries, 8.4% in Awash Fentale and 5.2% household respondents in Amibara woreda reported that pricked by thorns of P. juliflora [83].…”
Section: Effect Of P Juliflora On Human Healthmentioning
confidence: 99%
“…gender differences in Ethiopia's Amibara district, with men more likely to have perceived the species negatively compared to women (Seid et al, 2020). There were gender determinants of beliefs about water pollution in Burkina Faso, for example, where women expressed a strong belief that pesticides cause deterioration of water quality (Diendéré et al, 2018).…”
Section: Erential Perceptions Of Environmental Degradationmentioning
confidence: 99%